Cigarette Consumption and its Impact on Farmers Expenditure (Case Study of Samatan Village, Proppo Sub-District, Pamekasan Regency) - Nugraha Maulana Utama; Syarif Imam Hidayat; Gyska Indah Harya (Dinasti International Journal of Education Management And Social Science, 2025)
Cigarettes have emerged as a significant commodity in Indonesia, notably impacting household expenditures, particularly among farmers. The Central Bureau of Statistics (BPS) has categorized cigarettes within the food group due to their substantial influence on the Food Poverty Line (FPL). In 2023, data from BPS Kabupaten Pamekasan indicated that cigarette expenditure per capita ranked second, following food and processed drinks. This trend is not confined to urban areas; it has permeated rural households, including those of farmers. This study aims to analyze the perceptions, motivations, and meanings associated with cigarette consumption among farmers in Samatan Village, as well as its impact on their household expenditures. Utilizing primary data from in-depth interviews and questionnaires, alongside secondary data from relevant literature and documentation, the findings reveal a strong connection between farmers and smoking. Motivations for continued smoking stem from familial and social influences, leading to a significant portion of their daily expenses being allocated to cigarettes rather than food or other necessities. The study concludes that, within the socio-cultural and economic context of Samatan Village, cigarette consumption parallels food expenditure levels. This underscores the necessity for policy harmonization and a comprehensive approach to address cigarette consumption issues, particularly among farmers.